A new gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae) from the marine fish Terapon jarbua (Forsskål) (Terapontidae) off the eastern coast of India - Moravec, František; Gopalakrishnan, Ayyaru; Rajkumar, Mayalagu; Saravanakumar, Ayyapan; Kaliyamoorthy, Sinduja (Systematic parasitology, 2011)
A new nematode species, Philometra terapontis n. sp. (Philometridae), is described from male and female specimens found in the ovary of the jarbua terapon Terapon jarbua (Forsskål) (Terapontidae, Perciformes) from the Bay of Bengal off the eastern coast of India. Based on light and scanning electron microscopical examination, the new species differs from most other gonad-infecting Philometra spp. in the length of the spicules (105-114 μm), a gubernaculum with dorsal, lamella-like structures and a distinct protuberance on its distal end, and a U-shaped, dorsally uninterrupted caudal mound in the male. From a few congeneric, gonad-infecting species with unknown males, it can be distinguished by morphological and biometrical features found in gravid females (i.e. length of body, length of first-stage larvae or oesophagus, and caudal structure), by the host type (fish family) and by the geographical distribution. Philometra terapontis is the first philometrid species reported from a fish belonging to the family Terapontidae. Philometra sawara Quiazon, Yoshinaga & Ogawa, 2008 is considered a junior synonym of P. scomberomori (Yamaguti, 1935). A key to gonad-infecting species of Philometra parasitising marine and brackish-water fishes is provided.
Keywords: Animals; Seawater; Female; ženské pohlaví; Microscopy, Electron, Scanning; Perciformes; India; uterus; Uterus; mikroskopie elektronová rastrovací; Gonads; gonády; Dracunculoidea; Esophagus; Male; ezofágus; mořská voda; Larva; zvířata; mužské pohlaví; Indie; larva